The important role of mass transfer limitations caused by long chain fatty acids accumulation onto the anaerobic sludge - Pereira, M. A. (2004)
In this work, the role of transport limitations caused by LCFA accumulation onto anaerobic sludge was evaluated. Two sludges were compared in terms of the specific methanogenic activity in the presence of acetate, propionate, butyrate and H2/CO2, before and after the mineralization of LCFA accumulated onto the biomass. In both cases the main LCFA accumulated was palmitic acid, but in one of the sludges (referred as encapsulated sludge) it was mainly adsorbed, surrounding the cells, and in the other (non-encapsulated sludge) it was mainly precipitated in white spots in between the sludge. The LCFA loaded, but nonencapsulated sludge exhibited a considerable initial methanogenic activity on all the tested substrates, with the single exception of butyrate. However, for the encapsulated sludge only methane production from ethanol and H2/CO2 was detected, after a lag phase of about 50 hours. The obtained results evidenced that, besides the potential toxic effect, LCFA accumulation onto the sludge can create a physical barrier and hinder the transfer of substrates and products, inducing a delay on the initial methane production.